Transkripsi struktur penyajian lakon Rabine Panji pada kelompok wayang topeng tradisi Kedungmonggo Malang - Pratamawati, E.W. Suprihatin Dyah; Wahyuningtyas, Tri; Hartono, Hartono (citeus, 2016)
Malang is popular with one of its traditional dance that is Malang Puppet Mask (Wayang Topeng Malang, shortened into WTM). WTM has several characteristics, they are: (1) retelling Panji stories; (2) all dancers wear puppet mask with its own characters; (3) puppet master is usually performed by male and is responsible to tell stories and narrate the dialogs; (4) the stage has its definite patterns and cannot be changed according to the puppet master’s will. Panji’s stories and narration are based on folk lore so that the form and the structure are based on the puppet master’s memories, perception and variation, WTM artists, and the society. Sanggar Asmoro Bangun as one of WTM groups, located in Kedungmonggo village, Malang District, presents the dance into two versions, they are: (1) full duration to perform Rabine Panji (Panji’s Marroage); and (2) short version in performing Rabine Panji. Both versions influence several aspects in performing the dances, such as, the structure, the time, the scenes and the music.